(untitled) (Islas, 2023)
Introduction: The objective of this work is to deconstruct underlying elements between the material, the symbolic and their networks of signification present in the architecture of Catholic schools in Camagüey, Cuba (1900-1961) as a socio-formative space. Methods: A holistic approach that integrates knowledge from Pedagogy, Anthropology, Culturology, History, Sociology and Architecture is used. Methods used were documentary review, observation and the application of life histories to former students. Results: Multiple discriminations by skin color, sex, social class and territory associated with school architecture are revealed in terms of conditions, spatial distribution of buildings and the participation of socializing agents. Conclusions: The analysis establishes relationships from the macro with the structural, historical, cultural and institutional and from the micro with: the classroom context and the distribution of internal spaces. Power relations are revealed from the visual-constructed, the disciplinary system and its devices. The prevailing ideology is transmitted until its naturalization and internalization.